Design and Implementation of Anti-windup PI Control on DC-DC Bidirectional Converter for Hybrid Vehicle Applications - Muh. Zakiyullah Romdlony; Amin Amin (National Research and Innovation Agency, 2012)
Well-regulated DC bus voltage is the important point to guarantee the power demand in hybrid vehicle applications. Voltage regulation can be achieved with control method that build switching signal on DC-DC converter. This paper describes design and small scale experimental results of bus voltage regulation control of the DC-DC bidirectional converter with battery and supercapacitor as energy source. The control system consists of two control loops, the outer loop that get DC bus voltage feedback using PI anti-windup back calculation control method. This outer loop will generate a reference current for the inner loop that implement hysteresis control. The inner control loop will compare that reference curent with the source current obtained from the current sensor. Simulation and experimental results show that bus voltage is well-regulated under the load changes with 1% voltage ripple.